TECHNIKI OBRAZOWANIAThe role of multislice computed tomography in diagnosis of partial anomalous pulmonary venous connection in adults on the basis of selected cases - Głowacki, Jan; Miszalski-Jamka, Karol; Wasilewski, Jarosław; Jarski, Piotr; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital heart disease in adults. Multislice computed tomography is the method of choice in diagnosing unclear changes in chest suggesting a vascular origin of the disorder. Based on two cases of PAPVC in adults we discuss the role of computed tomography in the diagnostic process of this congenital heart disease.